Navigating Legal Complexities in Localising the Sustainable Development Goals Agenda for Village Governance in Indonesia - HS Tisnanta; Febryani Sabatira; Ria Wierma Putri; Lenilde Pereira; Desia Rakhma Banjarani (Sriwijaya Law Review, 2024)
Indonesia's commitment to the global Sustainable Development Goals (SDGs) is exemplified by its Village SDGs program, which serves as a strategic pilot initiative. Nevertheless, the efficacy of the Village SDGs is contingent upon several critical factors, including resource availability, community engagement, and stakeholder collaboration. These factors present significant challenges that impede progress. Given that villages constitute 91% of Indonesia's territory, developments at this local level have profound implications for the national implementation of the SDGs. This study elucidates that persistent challenges in resource allocation and stakeholder coordination remain despite advancements in embedding the SDGs within the national legal framework. The assessment of the Village SDGs highlights local capacity disparities and underscores the necessity for enhanced support mechanisms. Integrating the SDGs within village governance necessitates tailored approaches that are sensitive to local contexts. This paper establishes a comprehensive framework for the Village SDGs roadmap within local governance to achieve the global agenda. It explores three pivotal aspects, namely the incorporation of the SDGs into the national legal framework, the evaluation of Village SDGs implementation, and the contextualisation of the SDGs within village governance. Employing a normative legal approach and secondary data sources, the research reveals significant progress while also identifying critical gaps that must be addressed to ensure the effective implementation of the Village SDGs.